View: The clamour…and silence…over MSP in the farm bills - Roy, Devesh; Meenakshi, J. V. (Times Group, 2020)
The MSP system, in place since the mid-1960s, was part of the country’s drive to reduce dependence on food imports. It was an integral part of a package that included subsidized inputs meant to incentivize farmers to adopt new technologies and enhance farm productivity. The MSP was meant to protect farmers against price crashes that could occur with large harvests.